Найдите значение выражение b (b-2)x (b-6)x (b-8) при b=13

Найдите значение выражение b (b-2)x (b-6)x (b-8) при b=13
Гость
Ответ(ы) на вопрос:
Гость
b(b-2)*(b-6)*(b-8) = (b²-2b)*(b-6)*(b-8) = (b³-6b²-2b²+12b)*(b-8) = (b³-8b²+12b)*(b-8) = b⁴-8b³+12b²-8b³+64b²-96b = b⁴-16b³+76b²-96b =  13⁴-16*13³+76*13²-96*13 = 28561-16*2197+76*169-1248 =                     28561-35152+12844-1248 = -6591+12844-1248 = 6253-1248 = 5005. или b(b-2)*(b-6)*(b-8) = 13*(13-2)*(13-6)*(13-8) = 13*11*7*5 = 143*7*5 = 1001*5 = 5005.
Гость
И так (13-2)*(13-6)*(13-8)= 1)13-2=11 2)13-6=7
Не нашли ответ?
Ответить на вопрос
Похожие вопросы